TEHNIK ANALISIS MODEL LOGIT DAN PROBIT UNTUK PENELITIAN DALAM BERBAGAI BIDANG ILMU - Sidik Budiono (Universitas Sains dan Teknologi Jayapura, 2012)
We frequently face natural and social phenomen together. There are quantitative or/and qualitative data. Solving to econometrics analysis is not easy to apply because of some basic assumptions must be required. This paper want to explain how we make solution for quantitative or/and qualitative data for analysis. Logit and Probit model have some advantages and weakness as data type themselves.